Wsparcie uczniów z niepełnosprawnościami uczęszczających do szkół ogólnodostępnych i integracyjnych oraz ich nauczycieli przez tzw. dodatkowe osoby dorosłe - założenia wynikające z przepisów prawa oświatowego a szkolna rzeczywistość = Support of students with disabilities attending mainstream and integrated schools and their teachers by so-called additional adults - assumptions under educational law vs. school reality - Gołubiew-Konieczna, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is a compilation of information on one of the forms of supporting students with disabilities in mainstream and integrated schools, consisting in the presence of additional adults there. The author presents the tasks of a teacher with a background in special education co-organizing the educational process, a teacher`s aide, an assistant for a student with special educational needs, a special educator, specialists from the Specialized Center for Supporting Inclusive Education. It refers to the current educational legislation, completed and ongoing pilots promoted by the MEiN,school educational reality.
Keywords: uczeń niepełnosprawny; dodatkowe osoby dorosłe w szkole ogólnodostępnej; ustawodawstwo oświatowe; student with disabilities; additional adults in a mainstream school; educational legislation